An integrated methodological framework for the durable conservation of freshwater ecosystems: a case study in Colombia’s Caquetá River basin - Nogales, Jonathan; Rogéliz-Prada, Carlos; Cañon, Miguel A.; Vargas-Luna, Andres (Frontiers in Environmental Science, 2023)
Introduction: Although freshwater ecosystems encompass 12% of all known species, their study has achieved less progress in systematic conservation planning exercises compared with terrestrial and marine ecosystems. Moreover, little attention has been given to ecosystem services and cultural and spiritual values, which are pivotal in the long-term preservation of freshwater ecosystems. Conservation, restoration, and sustainable management actions within freshwater systems are currently addressed individually, underscoring the necessity of comprehensive methodological frameworks that holistically address the questions of where and how to conserve while integrating ecosystem services and cultural factors as conservation values. Methods: We propose a new methodological framework for the conservation of freshwater ecosystems that incorporates these elements and fulfills six prioritization criteria: i) representativeness, ii) integrity, iii) importance, iv) rarity, v) complementarity, and vi) connectivity. To illustrate the application of this approach, we conducted a regional study in the Caquetá River basin in Colombia. Results: By applying our methodological framework, we demonstrated that the Caquetá River basin hosts 518 distinct freshwater groups with unique characteristics that contribute to the maintenance of ecosystems and the preservation of their inherent values. Additionally, our analysis revealed that protection is the most effective conservation strategy for 77.4% of the Caquetá River basin, whereas restoration and sustainable management are suitable for 4.7% and 17.9% of the basin, respectively. The prioritized portfolio for the Caquetá River basin encompasses 80.1% of all freshwater groups, effectively meeting The Nature Conservancy's proposed conservation objectives. Conclusion: This novel methodological framework provides a pragmatic approach to systematic conservation planning and answers the questions of both where and how to conserve.